Allelic variation and heterosis in maize: How do two halves make more than a whole? - Springer, Nathan M.; Stupar, Robert M.

(untitled) (Genome Research, 2007)
In this review, we discuss the recent research on allelic variation in maize and possible implications of this work toward our understanding of heterosis. Heterosis, or hybrid vigor, is the increased performance of a hybrid relative to the parents, and is a result of the variation that is present within a species. Intraspecific comparisons of sequence and expression levels in maize have documented a surprisingly high level of allelic variation, which includes variation for the content of genic fragments, variation in repetitive elements surrounding genes, and variation in gene expression levels. There is evidence that transposons and repetitive DNA play a major role in the generation of this allelic diversity. The combination of allelic variants provides a more comprehensive suite of alleles in the hybrid that may be involved in novel allelic interactions. A major unresolved question is how the combined allelic variation and interactions in a hybrid give rise to heterotic phenotypes. An understanding of allelic variation present in maize provides an opportunity to speculate on mechanisms that might lead to heterosis. Variation for the presence of genes, the presence of novel beneficial alleles, and modified levels of gene expression in hybrids may all contribute to the heterotic phenotypes.